Les Écossais en France: a modern diaspora?. (4th March 2017) - Leith, Murray Stewart; Sim, Duncan
ABSTRACT: This paper examines the contemporary Scottish diaspora living and working in France. It considers the makeup, origins, drivers and influences of the diaspora, as well as considering the attitudes and behaviour of the diaspora itself. Through face to face interviews the paper considers the identity held by individuals within the diaspora, organisations they are (or are not) involved with and how they interact with the host country. It also considers diaspora attitudes held towards the homeland, and towards contemporary socio-political events taking place within Scotland today. The paper discusses the modern nature of the diaspora, the strong sense of national identity it holds, and how the Scottish Government may not be connecting with this diaspora at all.